Neuroendoscopic surgery for septated chronic subdural hematoma - Liu, Shelin; Liu, Fei; Cai, Zheng; Zhao, Xudong (Frontiers in Surgery, 2026)
ObjectiveTo explore the clinical efficacy of neuroendoscopic surgery in the treatment of septated chronic subdural hematomas (sCSDH).MethodsA retrospective analysis was conducted on the clinical data of 97 patients with sCSDH admitted to the Department of Neurosurgery, Wuxi Second People's Hospital from June 2019 to March 2025. Among them, patients who underwent traditional burr hole drainage under local anesthesia were assigned to the traditional burr hole drainage group (control group, n = 52), and those who underwent neuroendoscopic subdural hematoma evacuation under general anesthesia were assigned to the neuroendoscopic surgery group (observation group, n = 45). Perioperative indicators, Glasgow Coma Scale (GCS) score, Markwalder grade, neurological function scores before and after surgery, complications, and hematoma recurrence within 3 months of follow-up were compared between the two groups.ResultsBefore surgery, there were no significant differences in perioperative indicators, GCS score, Bender grade, or Markwalder grade between the two groups (P > 0.05). The observation group showed better intraoperative blood loss, drainage tube indwelling time, and immediate postoperative hematoma clearance rate than the control group (P < 0.05), while the total operation time of the control group was shorter than that of the observation group (P < 0.05). After surgery, neurological function scores improved in both groups (P < 0.05), but there was no significant difference between the two groups (P > 0.05). At different time points after surgery, GCS scores decreased in both groups (P < 0.05), and the scores in the observation group were lower than that in the control group (P < 0.05). There were no significant differences in the total complication rate or length of hospital stay between the two groups (P > 0.05), but the hematoma recurrence rate in the observation group was lower than that in the control group (P < 0.05).ConclusionBoth neuroendoscopic surgery and traditional burr hole drainage are effective in the treatment of sCSDH. However, neuroendoscopic surgery achieves a higher hematoma clearance rate, better recovery of consciousness, neurological function, and activities of daily living, and a lower postoperative recurrence rate, making it worthy of clinical promotion.